Ingesta dietética y actividad física en el tiempo libre de adultas-mayores en ámbito rural mediterráneo - Ruiz-Montero, Pedro Jesús; Martín-Moya, Ricardo (Archivos Latinoamericanos de Nutricion, 2017)
Elderly women in rural areas have a strong role in household and farming work, and they show food intake and use of leisure time. It is interesting to compare the differences between groups of elderly women of rural villages according to type of consumed food and energy expenditure during physical activity. A total of 117 women aged between 60 and 79 years who attended a physical fitness program in rural areas of Malaga province (Spain) participated in this study. The participants were classified in different energy expenditure groups: sedentary (less than 1.250METs-min/14 days), moderately active (1.250-2.999 METs-min/14 days), active (3.000-4.999 METs-min/14 days) and highly active (over 5.000 METs-min/14 days). Sociodemographic and clinical characteristics of participants (body mass index hypertension and food habits) were measured. The results indicate that the oldest participants are in the sedentary group or in the highly active group (p<0.001). In addition, the sedentary group shows higher weight and body mass index (p<0.001; p<0.01, respectively), and the moderately active group consumes more vegetables (p<0.01). In conclusion, a rich diet of vegetables, fruits with a control of red meat intake could induce to decrease of BMI in participants.
Dietary intake and physical activity in leisure time of adult-elderly women in Mediterranean rural areas
Keywords: gasto energético; ingesta; alimentos; actividad física; rural; energy expenditure; intake; food; physical activity; JCR; Scopus